Time trends in prostate cancer mortality according to major geographic regions of Brazil: an analysis of three decades - Mara Beatriz Martins Conceição; Antonio Fernando Boing; Karen Glazer Peres (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2014)
The aim of this study was to analyze prostate cancer mortality and time trends in Brazil, according to major geographic regions, States, and age brackets. Data on deaths from 1980 to 2010 were obtained from the Mortality Information System. Mortality trends were estimated using Prais-Winsten generalized linear regression. An upward time trend was observed in mortality in all regions of Brazil, with a mean annual increase of 2.8%. The upward trend in mortality occurred in most of the age brackets, with a concentration of deaths in men 70 to 79 years of age (41%) and a significant increase in the 40 to 60-year age bracket. The mortality rate increased significantly in all age brackets in the Northeast, compared to the other regions of Brazil. The study highlighted the importance of redistributing deaths from ill-defined causes in order to correct the mortality rates. The results point to significant regional differences and the need for continuous monitoring of mortality from prostate cancer in Brazil.